2018
DOI: 10.5205/1981-8963-v12i4a231030p1174-1178-2018
|View full text |Cite
|
Sign up to set email alerts
|

Implementação e implantação da sistematização da assistência de enfermagem

Abstract: RESUMOObjetivo: relatar a experiência da criação de uma comissão para a implantação da Sistematização da Assistência de Enfermagem. Método: estudo descritivo, tipo relato de experiência, realizado em novembro de 2017. A comissão foi designada pela Divisão de Enfermagem com a finalidade de implantar a SAE na instituição e o software para a prescrição de Enfermagem. A comissão desenvolveu seu regimento interno e promoveu treinamentos aos seus enfermeiros para capacitá-los quanto ao uso da ferramenta, etapas da S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
9

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 3 publications
(3 reference statements)
0
1
0
9
Order By: Relevance
“…A study that aimed to analyze the contribution of NCS to the hospital audit (7) identified that when it is performed effectively, this in itself is comprehensiveness associated with the quality of care provided to the client, also collaborating in reducing hospitalization time and in less financial losses for health institutions. Also, the creation of institutional commissions has been reported as essential to the implementation of nursing care, training and awareness of nursing professionals regarding NCS and NP (21) .…”
Section: Discussionmentioning
confidence: 99%
“…A study that aimed to analyze the contribution of NCS to the hospital audit (7) identified that when it is performed effectively, this in itself is comprehensiveness associated with the quality of care provided to the client, also collaborating in reducing hospitalization time and in less financial losses for health institutions. Also, the creation of institutional commissions has been reported as essential to the implementation of nursing care, training and awareness of nursing professionals regarding NCS and NP (21) .…”
Section: Discussionmentioning
confidence: 99%
“…Frente a isso, arrazoa-se que a formação de uma comissão para o processo de enfermagem permite que o serviço entre em concordância com as atribuições dos enfermeiros e a organização da assistência de enfermagem. Da mesma forma, possibilita a capacitação dos profissionais quanto à realização do processo de enfermagem, tornando-se factível a afirmação de que a presença de comissões dessa natureza podem contribuir com a implementação e gestão do processo de enfermagem (19) .…”
Section: Discussionunclassified
“…Além disso, proporciona autonomia para a profissão, por representar uma metodologia de assistência reconhecida pelos enfermeiros, bem como permitir uma aproximação junto ao paciente. Assim, cabe a importância da instituição em apoiar e valorizar essa proposta para facilitar o trabalho do enfermeiro e a adesão do paciente ao processo (23,24) .…”
Section: Discussionunclassified